Composite antistatic table mat and preparation method thereof

By using conductive titanium dioxide and vinyl MQ silicone resin with particle size of 150nm-250nm, composite antistatic stage pads were prepared, which solved the problems of high surface resistance and low conductivity of existing stage pads, and achieved low Resistivity, long-lasting conductivity and good wear resistance.

CN119427848AActive Publication Date: 2025-02-14GUANGDONG SILICON LEATHER TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411543735.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing platform pad made of conductive titanium dioxide has the problem of high surface resistance and insufficient conductivity.

Method used

A composite antistatic stage pad is prepared by using conductive titanium dioxide with a particle size of 150nm-250nm, combined with raw materials such as vinyl MQ silicone resin, including an antistatic layer, an adhesive layer and a conductive silicone layer. Through specific preparation The process improves the conductivity and wear resistance of the table pad.

Benefits of technology

A composite anti-static stage pad with low volume resistivity, long-lasting conductivity and stable performance is achieved, which improves the wear resistance and anti-static performance of the stage pad.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113320870000091
    Figure BDA0005113320870000091
  • Figure BDA0005113320870000101
    Figure BDA0005113320870000101
Patent Text Reader

Abstract

The invention relates to a table mat, in particular to a composite antistatic table mat and a preparation method, the composite antistatic table mat comprises an antistatic layer, the raw material of the antistatic layer comprises conductive titanium dioxide, and the composite antistatic table mat is characterized in that the particle size of the conductive titanium dioxide is 150-250 nm; the preparation method comprises the steps of preparation of the antistatic layer, preparation of the bonding layer, coating of the antistatic layer and preparation of the composite antistatic table pad. The anti-static layer of the table mat adopts the conductive titanium dioxide with the particle size of 150-250 nm, so that the wear resistance of the anti-static layer is improved, the surface resistance of the anti-static layer is reduced, and the electric conductivity is lasting and stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a table mat, in particular to a composite antistatic table mat and a preparation method thereof. Background Art

[0002] Antistatic table mats are mainly made of static materials, static dissipative materials and synthetic rubber through a variety of processes. They are usually made of double-layer composite structures. The surface layer is a dissipative static layer of about 0.3-0.5mm thick, with a resistance of 106-109Ω, and the bottom layer is a conductive layer of about 1.5-1.7mm thick, with a resistance of 103-105Ω. Antistatic table mats have a long service life, so the material is required to be soft, strong in rebound, tear-resistant, wear-resistant, easy to clean, not affected by high temperature, severe cold and humidity, low in volume resistivity, long-lasting conductivity, and stable technical index.

[0003] The anti-static mats on the market are mainly made of polyvinyl chloride (PVC) or nitrile rubber (NBR). The production and use of PVC will produce some harmful substances, such as dioxins, vinyl chloride monomer, etc., which are potentially harmful to human health and the environment. PVC has poor heat resistance and is easy to decompose and produce harmful gases at high temperatures. Under long-term sunlight, PVC products are prone to aging, discoloration and other problems, which affects the appearance and service life of PVC products. NBR has the disadvantages of poor low temperature resistance, poor ozone resistance and poor insulation performance.

[0004] Conductive titanium dioxide (conductive titanium dioxide) is based on titanium dioxide. It uses nanotechnology, surface treatment, and semiconductor doping to form a conductive oxide layer on the surface of the matrix, thereby producing a new type of electronic conductive functional semiconductor pigment (filler). Conductive titanium dioxide absorbs less light, has a large scattering ability, and has good optical properties such as gloss, whiteness, tinting power, and hiding power. It can be made into near-white and other light-colored permanent conductive and anti-static products. It is particularly suitable for conductive and anti-static products and environments with high whiteness requirements. It is non-toxic and odorless, acid-resistant, alkali-resistant, salt-resistant, organic solvent-resistant, light-resistant, stable below 800°C, non-oxidizing, non-flammable, and flame-retardant. It is suitable for almost any environment and occasion that requires conductivity and anti-static. By adding it to coatings, plastics, rubber, adhesives, inks, cement, fibers, and ceramics, and combining it with other pigments, it can be easily formulated into permanent conductive and antistatic products in various colors such as near white. It can be widely used in various industrial sectors such as petroleum, chemical industry, building materials, electronics, electromechanical, communications, automobiles, medicine, papermaking, textiles, packaging, printing, ships, ceramics, aerospace, weapons, and the conductive and antistatic fields in people's daily lives.

[0005] However, the existing table pads made of conductive titanium dioxide have the disadvantages of high surface resistance and short-lasting conductivity. Summary of the invention

[0006] In order to solve the above technical problems, the purpose of the present invention is to provide a composite antistatic table mat with low volume resistivity and long-lasting conductivity and a preparation method thereof.

[0007] The technical solution adopted by the present invention to solve the problem is: a composite antistatic table mat, including an antistatic layer, the raw material of the antistatic layer includes conductive titanium dioxide, and the characteristic is that the particle size of the conductive titanium dioxide is 150nm-250nm.

[0008] As a further improvement of the above technical solution, the particle size of the conductive titanium dioxide is 150-200 nm.

[0009] As a further improvement of the above technical solution, the raw material of the antistatic layer also includes vinyl MQ silicone resin.

[0010] As a further improvement of the above technical solution, the viscosity of the vinyl MQ silicone resin is 20000 cs.

[0011] As a further improvement of the above technical solution, it also includes an adhesive layer and a conductive silicone layer, and the adhesive layer is located between the antistatic layer and the conductive silicone layer.

[0012] As a further improvement of the above technical solution, the antistatic layer is made of the following raw materials in parts by weight: 5-15 parts of vinyl silicone rubber base glue, 30-50 parts of vinyl MQ resin, 10-30 parts of conductive titanium dioxide, 5-15 parts of the first high hydrogen silicone oil, 1-3 parts of the first silane coupling agent, 0.5-1 parts of the first platinum catalyst, and 0.02-0.1 parts of the first inhibitor; the adhesive layer is made of the following raw materials in parts by weight: 50-70 parts of liquid glue, 10-20 parts of vinyl silicone oil, 5-10 parts of the second high hydrogen silicone oil, 1-3 parts of the second silane coupling agent, 0.5-1 parts of the second platinum catalyst, and 0.02-0.1 parts of the second inhibitor; the preparation steps are as follows: S1: Add the vinyl silicone rubber base glue, vinyl MQ resin, conductive titanium dioxide, the first high hydrogen silicone oil, the first silane coupling agent, The coupling agent, the first platinum catalyst and the first inhibitor are put into a disperser and stirred for 10-20 minutes to obtain the raw material for the antistatic layer; S2: the liquid glue, vinyl silicone oil, the second high hydrogen silicone oil, the second silane coupling agent, the second platinum catalyst and the second inhibitor are put into a disperser and stirred for 10-20 minutes to obtain the raw material for the adhesive layer; S3: the raw material for the antistatic layer is coated on release paper or leather paper, and is conveyed to a tunnel oven by a conveyor belt, and baked at a temperature of 110-130°C for 5-8 minutes to form an antistatic layer; S4: the raw material for the adhesive layer is first coated on the upper surface of the antistatic layer, and then the conductive silicone layer is attached to the top of the antistatic layer, and it is conveyed to the tunnel oven, and baked at a temperature of 110-130°C for 5-8 minutes to obtain a composite antistatic table mat.

[0013] As a further improvement of the above technical solution, the first silane coupling agent and the second silane coupling agent are one or a mixture of two or more of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, KH-560, and KH-570; the first inhibitor and the second inhibitor are one or a mixture of two of ethynyl cyclohexanol and diallyl maleate.

[0014] As a further improvement of the above technical solution, the thickness of the antistatic layer is 0.02-0.05 mm; the thickness of the adhesive layer is 0.1-0.5 mm; and the thickness of the conductive silicone layer is 0.9-1.2 mm.

[0015] The beneficial effects of the present invention are as follows: the antistatic layer of the table mat of the present invention adopts conductive titanium dioxide with a particle size of 150nm-250nm, thereby improving the wear resistance of the antistatic layer and reducing the surface resistance of the antistatic layer, and the conductivity is durable and stable. DETAILED DESCRIPTION

[0016] In all embodiments of the present invention, unless otherwise specified about temperature and pressure, all are at room temperature and pressure, and unless otherwise specified about the use of equipment, all can be used according to conventional settings.

[0017] To make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0018] It is to be understood that these descriptions are exemplary only and are not intended to limit the scope of the invention.

[0019] Embodiment 1: A method for preparing a composite antistatic table mat, which comprises an antistatic layer, an adhesive layer and a conductive silicone layer from bottom to top.

[0020] The antistatic layer is composed of the following raw materials: 8 parts of vinyl silicone rubber base, 40 parts of vinyl MQ resin (which can be but is not limited to Longsheng Sihai SH-5202), 20 parts of conductive titanium dioxide, 8 parts of the first high hydrogen silicone oil, 1 part of the first silane coupling agent, 0.5 parts of the first platinum catalyst, and 0.02 parts of the first inhibitor; the viscosity of the vinyl MQ resin is 20000cs; the particle size of the conductive titanium dioxide is 150nm.

[0021] The adhesive layer is composed of the following raw materials: 60 parts of liquid glue (can be but not limited to Zhengan silicone GA-2075), 20 parts of vinyl silicone oil, 8 parts of the second high hydrogen silicone oil, 1 part of the second silane coupling agent, 0.5 parts of the second platinum catalyst, and 0.02 parts of the second inhibitor.

[0022] The conductive silicone layer is formed by calendering of antistatic liquid glue (which may be but is not limited to Zhengan silicone GA-2024), with a thickness of 1 mm and a conductivity of 9-12. The hardness of the antistatic liquid glue after molding is 20A.

[0023] The vinyl content in the vinyl silicone rubber base is 0.5%; the viscosity of the vinyl silicone oil is 500cs, and the vinyl content is 5.0%; the silane coupling agent (the first silane coupling agent and the second silane coupling agent) is a mixture of KH-560 and KH-570; the platinum catalyst (the first platinum catalyst and the second platinum catalyst) is a 5000ppm ethanol solution; the inhibitor (the first inhibitor and the second inhibitor) is diallyl maleate.

[0024] The thickness of the antistatic layer is 0.05 mm; the thickness of the adhesive layer is 0.1 mm; and the thickness of the conductive silicone layer is 1.2 mm.

[0025] The preparation steps of Example 1 are as follows:

[0026] S1: Put the above-mentioned vinyl silicone rubber base, vinyl MQ resin, conductive titanium dioxide, the first high hydrogen silicone oil, the first silane coupling agent, the first platinum catalyst and the first inhibitor in a disperser and stir for 15 minutes to obtain the antistatic layer raw material.

[0027] S2: Put the above-mentioned liquid glue, vinyl silicone oil, second high hydrogen silicone oil, second silane coupling agent, second platinum catalyst and second inhibitor in a dispersing mixer, disperse and stir for 15 minutes to obtain a bonding layer raw material.

[0028] S3: coating the antistatic layer raw material on release paper or leather paper, conveying it to a tunnel oven through a conveyor belt, and baking it at a temperature of 130° C. for 5 minutes to form an antistatic layer.

[0029] S4: firstly apply the adhesive layer raw material on the upper surface of the antistatic layer, then adhere the conductive silicone layer on the top of the antistatic layer, transfer it to a tunnel oven, bake it at 110°C for 8 minutes, tear off the release paper or leather paper, and obtain Example 1.

[0030] Embodiment 2: A method for preparing a composite antistatic table mat, which comprises, from bottom to top, an antistatic layer, an adhesive layer and a conductive silicone layer.

[0031] The antistatic layer is composed of the following raw materials: 15 parts of vinyl silicone rubber base, 50 parts of vinyl MQ resin, 25 parts of conductive titanium dioxide, 10 parts of the first high hydrogen silicone oil, 1 part of the first silane coupling agent, 0.5 parts of the first platinum catalyst, and 0.02 parts of the first inhibitor; the viscosity of the vinyl MQ resin is 10000cs; the particle size of the conductive titanium dioxide is 200nm.

[0032] The adhesive layer is composed of the following raw materials: 50 parts of liquid glue (which may be but is not limited to Zhengan silicone GA-2660), 15 parts of vinyl silicone oil, 8 parts of the second high hydrogen silicone oil, 1 part of the second silane coupling agent, 0.5 parts of the second platinum catalyst, and 0.02 parts of the second inhibitor.

[0033] The conductive silicone layer is formed by calendering of antistatic liquid glue (which may be but is not limited to Zhengan silicone GA-2034), with a thickness of 1 mm and a conductivity of 9-12. The hardness of the antistatic liquid glue after molding is 30A.

[0034] The vinyl content in the vinyl silicone rubber base is 0.3%; the viscosity of the vinyl silicone oil is 2000cs, and the vinyl content is 3.0%; the silane coupling agent (the first silane coupling agent and the second silane coupling agent) is 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane; the platinum catalyst (the first platinum catalyst and the second platinum catalyst) is a 5000ppm ethanol solution; the inhibitor (the first inhibitor and the second inhibitor) is ethynylcyclohexanol.

[0035] The thickness of the antistatic layer is 0.05 mm; the thickness of the adhesive layer is 0.2 mm; and the thickness of the conductive silicone layer is 1.0 mm.

[0036] The preparation steps of Example 2 are as follows:

[0037] S1. Preparation of antistatic layer: put the above-mentioned vinyl silicone rubber base, vinyl MQ resin, conductive titanium dioxide, the first high hydrogen silicone oil, the first silane coupling agent, the first platinum catalyst and the first inhibitor in a disperser and stir for 15 minutes to obtain the antistatic layer raw material.

[0038] S2. Preparation of adhesive layer: put the above-mentioned liquid glue, vinyl silicone oil, second high hydrogen silicone oil, second silane coupling agent, second platinum catalyst and second inhibitor in a disperser and stir for 15 minutes to obtain adhesive layer raw materials.

[0039] S3. Antistatic layer coating: Coat the antistatic layer raw material on release paper or leather paper, transfer it to the tunnel oven through a conveyor belt, and bake it at 110°C for 8 minutes to form an antistatic layer.

[0040] S4. Preparation of composite antistatic table mat: firstly, apply the adhesive layer raw material on the upper surface of the antistatic layer, then attach the conductive silicone layer on the top of the antistatic layer, transfer it to a tunnel oven, bake it at 130°C for 5 minutes, tear off the release paper or leather paper, and obtain Example 2.

[0041] Embodiment 3: The difference from Embodiment 1 is that the particle size of the conductive titanium dioxide is 250 nm.

[0042] Embodiment 4: The difference from Embodiment 2 is that the particle size of the conductive titanium dioxide is 250 nm.

[0043] Embodiment 5: The difference from Embodiment 1 is that the particle size of the conductive titanium dioxide is 130 nm.

[0044] Embodiment 6: The difference from Embodiment 2 is that the particle size of the conductive titanium dioxide is 130 nm.

[0045] Embodiment 7: The difference from Embodiment 1 is that the particle size of the conductive titanium dioxide is 300 nm.

[0046] Embodiment 8: The difference from Embodiment 2 is that the particle size of the conductive titanium dioxide is 300 nm.

[0047] Embodiment 9: The difference from Embodiment 1 is that the viscosity of the vinyl MQ resin is 10000 cs.

[0048] Embodiment 10: The difference from Embodiment 1 is that the viscosity of the vinyl MQ resin is 5000 cs.

[0049] Comparative Example 1: The difference from Example 1 is that the antistatic layer lacks the conductive titanium dioxide, and the comparative example 1 is prepared according to the coating process in Example 1.

[0050] Comparative Example 2: The difference from Example 2 is that the conductive silicone layer is made of 30A common liquid glue, and is prepared according to the coating process in Example 2.

[0051] The wear resistance and resistance of Examples 1 to 10 and Comparative Examples 1 and 2 obtained above were tested, and the results are as follows:

[0052]

[0053]

[0054] Among them, TABER wear resistance: the test was conducted in accordance with the reference standard QB / T 2726-2005, using H-22 grinding wheel, 1000g load, 1000 test times, and 60rpm speed. The evaluation criteria are: Level 1 - obvious wear; Level 2 - relatively obvious wear; Level 3 - slight wear; Level 4 - difficult to distinguish wear; Level 5 - indistinguishable wear;

[0055] Steel wool abrasion resistance test: Tested with reference to ASTM F2496, sample size: 5*5cm; steel wool model: Japanese #0000 steel wool; load: 500g weight; number of times: 2500 times; speed: 60rpm. The judging criteria are: Level 1 - steel wool is worn out, leather surface is obviously worn out; Level 2 - steel wool is partially worn out, leather surface is obviously worn out; Level 3 - steel wool is not damaged, leather surface is blackened; Level 4 - steel wool is not damaged, leather surface is slightly worn out; Level 5 - steel wool is not damaged, leather surface feels smooth, and wear cannot be distinguished.

[0056] From the above test results, it can be seen that when the particle size of the conductive titanium dioxide is 150nm-250nm, the surface resistance of the obtained mat is low and has good antistatic properties. When the particle size of the conductive titanium dioxide is less than 150nm or greater than 250nm, the surface resistance is between 10 9 -10 11 Ω, anti-static property is average.

[0057] The applicant also found that the viscosity of the vinyl MQ resin will also affect the antistatic properties of the antistatic layer. By comparing Examples 1, 9 and 10, the reduction in the viscosity of the vinyl MQ resin not only affects the wear resistance and durability of the antistatic layer, but also indirectly affects the antistatic properties of the antistatic layer. Preliminary research found that the antistatic layer with a viscosity of the vinyl MQ resin of 20,000 cs and a particle size of the conductive titanium dioxide of 150 nm has a lower resistance value and better antistatic properties.

[0058] The above implementation modes cannot limit the protection scope of the invention. Without departing from the spirit and scope of the invention, the invention may have various changes and improvements, and these changes and improvements all fall within the scope of the invention claimed for protection.

Claims

1. A composite antistatic table mat, comprising an antistatic layer, wherein the raw material of the antistatic layer comprises conductive titanium dioxide, characterized in that: The particle size of the conductive titanium dioxide is 150nm-250nm.

2. A composite antistatic table mat as claimed in claim 1, characterized in that: The particle size of the conductive titanium dioxide is 150-200 nm.

3. A composite antistatic table mat as claimed in claim 2, characterized in that: The raw material of the antistatic layer also includes vinyl MQ silicone resin.

4. A composite antistatic table mat as claimed in claim 3, characterized in that: The viscosity of the vinyl MQ silicone resin is 20000 cs.

5. A composite antistatic table mat as claimed in claim 4, characterized in that: It also includes an adhesive layer and a conductive silicone layer, wherein the adhesive layer is located between the antistatic layer and the conductive silicone layer.

6. A method for preparing a composite antistatic table mat, characterized in that: The antistatic layer is made of the following raw materials in parts by weight: 5-15 parts of vinyl silicone rubber base, 30-50 parts of vinyl MQ resin, 10-30 parts of conductive titanium dioxide, 5-15 parts of the first high hydrogen silicone oil, 1-3 parts of the first silane coupling agent, 0.5-1 parts of the first platinum catalyst, and 0.02-0.1 parts of the first inhibitor; The bonding layer is made of the following raw materials in parts by weight: 50-70 parts of liquid glue, 10-20 parts of vinyl silicone oil, 5-10 parts of second high hydrogen silicone oil, 1-3 parts of second silane coupling agent, 0.5-1 parts of second platinum catalyst, and 0.02-0.1 parts of second inhibitor; The preparation steps are as follows: S1: putting the weight proportions of the vinyl silicone rubber base, the vinyl MQ resin, the conductive titanium dioxide, the first high hydrogen silicone oil, the first silane coupling agent, the first platinum catalyst and the first inhibitor into a dispersing mixer, and dispersing and stirring for 10-20 minutes to obtain an antistatic layer raw material; S2: putting the liquid glue, vinyl silicone oil, the second high hydrogen silicone oil, the second silane coupling agent, the second platinum catalyst and the second inhibitor in the above-mentioned weight proportions into a dispersing mixer, and dispersing and stirring for 10-20 minutes to obtain a bonding layer raw material; S3: coating the antistatic layer raw material on release paper or leather paper, conveying it to the tunnel oven through a conveyor belt, and baking it at a temperature of 110-130° C. for 5-8 minutes to form an antistatic layer; S4: firstly apply the adhesive layer raw material on the upper surface of the antistatic layer, then attach the conductive silicone layer on the top of the antistatic layer, transfer it to a tunnel oven, bake it at a temperature of 110-130° C. for 5-8 minutes, and obtain a composite antistatic table mat.

7. The method for preparing a composite antistatic table mat according to claim 6, characterized in that: The first silane coupling agent and the second silane coupling agent are one or a mixture of two or more of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, KH-560, and KH-570; the first inhibitor and the second inhibitor are one or a mixture of two of ethynylcyclohexanol and diallyl maleate.

8. The method for preparing a composite antistatic table mat according to claim 6, characterized in that: The thickness of the antistatic layer is 0.02-0.05 mm; the thickness of the adhesive layer is 0.1-0.5 mm; and the thickness of the conductive silicone layer is 0.9-1.2 mm.

Citation Information

Patent Citations

  • Coated metal sheet

    CN108290383A

  • Antistatic organic-silicon synthetic leather and preparation method thereof

    CN109826021A

  • Light-color titanium dioxide conductive filler, and preparation method and application thereof

    CN112852208A

  • Permanent antistatic silica gel and preparation method thereof

    CN113337118A

  • High-fluidity liquid silicone rubber as well as preparation method and application thereof

    CN114276687A